근권세균 Bacillus sp. CT16과 Neobacillus sp. JC05의 배양액 추출물에 의한 뿌리혹 선충의 알 부화 억제 효과 - 장화진(Hwajin Jang); 김상태(Sang Tae Kim); 상미경(Mee Kyung Sang) (Sigmulbyeong yeon'gu, 2021)
Root-knot disease caused by Meloidogyne incognita is major soil pathogen and cause severe economic damages to vegetable crops. In this study, we selected rhizobacteria for biocontrol of the root-knot nematode, M. incognita, and identified; performed bioassay of the bacterial extracts in cucumber seedlings. The crude extracts of strains CT16 and JC05 out of 180 strains inhibited egg hatching and increased juvenile mortality in vitro assay; based on 16S rRNA sequences analysis, the two strains were identified as Bacillus sp. CT16, and Neobacillus sp. JC05. After extracting the bacterial supernatants by using various organic solvents, n-butanol and n-hexane extracts of strain CT16 and n-butanol extract of strain JC05 showed inhibitory activity of egg hatching depending on concentrations. Subsequently, n-butanol extracts of two strains significantly suppressed formation of egg masses in cucumber seedling. Therefore, these results indicated that strains CT16 and JC05 could be used as potential biocontrol agents against M. incognita. 식물 근권에서 180 균주를 분리하여 뿌리혹 선충(Meloidogyne incognita)의 알 부화율 억제 효과가 있는 34개 균주를 일차적으로 선발하였고, 이들 중 알 부화율과 유충 억제에 모두 효과가 있는 세균 JC05와 CT16을 선발하였다. 두 균주는 각각 Bacillus sp. CT16과 Neobacillus sp. JC05로 동정하였으며, 두 균주의 배양액을 용매로 추출 및 농축한 후 선충의 알 부화율을 평가한 결과, JC05의 n-butanol 추출물은 25 ㎍/ml이상의 농도에서 알의 부화를 효과적으로 억제했으며, CT16의 n-hexane과 n-butanol 추출물에서는 각각 25 ㎍/ml, 10 ㎍/ml 이상의 농도에서 알 부화를 효과적으로 억제하였다. 오이 유묘 식물에 검정한 결과, 100 ㎍/ml의 CT16와 JC05의 n-butanol 추출물을 오이 유묘에 처리했을 때, 뿌리에 감염된 난낭의 수가 감소하였다. 이를 통해 JC05와 CT16가 생성하는 대사산물이 알 부화율 억제 활성을 보이는 것으로 생각되며 JC05와 CT16의 n-butanol 추출물이 선충방제로서 사용 가능성을 제시할 수 있다. 이후에는 뿌리혹 선충 억제에 효과가 있는 추출물의 활성 물질을 동정하고 오이 식물에서 작용 메커니즘 규명하기 위한 연구를 수행하여 오이를 비롯한 박과류 뿌리혹 선충 억제를 위한 농업용 소재로 활용할 예정이다.